Value Management for Exploration Projects. Issue 4 (August 2014) - Maniak, Rémi; Midler, Christophe; Lenfle, Sylvain; Pellec‐Dairon, Marie Le
ABSTRACT Whereas exploration projects stand as important drivers in renewing the assets of the firm and creating new business opportunities, it is well recognized that project evaluation and value management methodologies are likely to kill them. This paper provides elements to solving this paradox. We rely on a longitudinal study of three exploration projects and the projects conducted afterward in the automotive and space industries. The analysis suggests that the value creation process can be regarded and managed as a dual process of potential value creation and value realization. This paper discusses the linkages with existing practices and theories.